Culture, choice and action in legume seeds systems in East and North Uganda - Njuguna-Mungai, Esther; Mesianto Lengewa, Catherine (International Crops Research Institute for the Semi-Arid Tropics, 2019)
Presented by Esther Njuguna-Mungai (ICRISAT) and Catherine Mesianto Lengewa (CBCC-Africa) on May 10, 2019, as part of the webinar 'Culture, choice and action in legume seeds systems in East and North Uganda'. The webinar was co-organized by the CGIAR Collaborative Platform for Gender Research and the CGIAR Research Program on Grain Legumes and Dryland Cereals.